Adhesion and Cohesion - J. Anthony von Fraunhofer (International Journal of Dentistry)
The phenomena of adhesion and cohesion are reviewed and discussed with particular reference to dentistry. This review considers the forces involved in cohesion and adhesion together with the mechanisms of adhesion and the underlying molecular processes involved in bonding of dissimilar materials. The forces involved in surface tension, surface wetting, chemical adhesion, dispersive adhesion, diffusive adhesion, and mechanical adhesion are reviewed in detail and examples relevant to adhesive dentistry and bonding are given. Substrate surface chemistry and its influence on adhesion, together with the properties of adhesive materials, are evaluated. The underlying mechanisms involved in adhesion failure are covered. The relevance of the adhesion zone and its importance with regard to adhesive dentistry and bonding to enamel and dentin is discussed.